Efficacy of a Web-Based Safety Decision Aid for Women Experiencing Intimate Partner Violence: Randomized Controlled Trial - Koziol-McLain, Jane; Vandal, Alain C; Wilson, Denise; Nada-Raja, Shyamala; Dobbs, Terry; McLean, Christine; Sisk, Rose; Eden, Karen B; Glass, Nancy E (Journal of medical Internet research, 2018)
Intimate partner violence (IPV) is a human rights violation and leading health burden for women. Safety planning is a hallmark of specialist family violence intervention, yet only a small proportion of women access formal services. A Web-based safety decision aid may reach a wide audience of women experiencing IPV and offer the opportunity to prioritize and plan for safety for themselves and their families. The aim of this study was to test the efficacy of a Web-based safety decision aid (isafe) for women experiencing IPV. We conducted a fully automated Web-based two-arm parallel randomized controlled trial (RCT) in a general population of New Zealand women who had experienced IPV in the past 6 months. Computer-generated randomization was based on a minimization scheme with stratification by severity of violence and children. Women were randomly assigned to the password-protected intervention website (safety priority setting, danger assessment, and tailored action plan components) or control website (standard, nonindividualized information). Primary endpoints were self-reported mental health (Center for Epidemiologic Studies Depression Scale-Revised, CESD-R) and IPV exposure (Severity of Violence Against Women Scale, SVAWS) at 12-month follow-up. Analyses were by intention to treat. Women were recruited from September 2012 to September 2014. Participants were aged between 16 and 60 years, 27% (111/412) self-identified as Māori (indigenous New Zealand), and 51% (210/412) reported at baseline that they were unsure of their future plans for their partner relationship. Among the 412 women recruited, retention at 12 months was 87%. The adjusted estimated intervention effect for SVAWS was -12.44 (95% CI -23.35 to -1.54) for Māori and 0.76 (95% CI -5.57 to 7.09) for non-Māori. The adjusted intervention effect for CESD-R was -7.75 (95% CI -15.57 to 0.07) for Māori and 1.36 (-3.16 to 5.88) for non-Māori. No study-related adverse events were reported. The interactive, individualized Web-based isafe decision aid was effective in reducing IPV exposure limited to indigenous Māori women. Discovery of a treatment effect in a population group that experiences significant health disparities is a welcome, important finding. Australian New Zealand Clinical Trials Registry (ANZCTR): ACTRN12612000708853; https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?ACTRN=12612000708853 (Archived by Webcite at http://www.webcitation/61MGuVXdK).